2012
DOI: 10.1007/s11948-012-9411-6
|View full text |Cite
|
Sign up to set email alerts
|

Midstream Modulation in Biotechnology Industry: Redefining What is ‘Part of the Job’ of Researchers in Industry

Abstract: In response to an increasing amount of policy papers stressing the need for integrating social and ethical aspects in Research and Development (R&D) practices, science studies scholars have conducted integrative research and experiments with science and innovation actors. One widely employed integration method is Midstream Modulation (MM), in which an 'embedded humanist' interacts in regular meetings with researchers to engage them with the social and ethical aspects of their work. While the possibility of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 35 publications
1
58
0
3
Order By: Relevance
“…With regard to enhancing anticipation, Arentshorst et al state that scientists and technology developers should not only engage in constructive technology assessment but also in 'vision assessment' that aims to make the guiding visions, which act as the driving forces behind expectations and promises, more explicit and assessed on their realistic value [109]. With regard to enhancing reflexivity, Flipse et al proposed that researchers with industrial motivations get in contact with humanists during the early stages of innovation to increase the researchers' awareness of social and ethical considerations in their work [110]. Foley et al proposed a new refined framework for responsible innovation that builds on the procedural dimensions of Stilgoe et al and the substantive approach by von Schomberg, including the idea of intraand inter-generational justice [111].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to enhancing anticipation, Arentshorst et al state that scientists and technology developers should not only engage in constructive technology assessment but also in 'vision assessment' that aims to make the guiding visions, which act as the driving forces behind expectations and promises, more explicit and assessed on their realistic value [109]. With regard to enhancing reflexivity, Flipse et al proposed that researchers with industrial motivations get in contact with humanists during the early stages of innovation to increase the researchers' awareness of social and ethical considerations in their work [110]. Foley et al proposed a new refined framework for responsible innovation that builds on the procedural dimensions of Stilgoe et al and the substantive approach by von Schomberg, including the idea of intraand inter-generational justice [111].…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of innovation management, we found literature that explicitly highlights KPIs for ongoing R&D processes, from a management/organizational perspective, from a practical/working floor perspective, and from the perspective of the outcomes of such processes, all from different fields of innovation, including empirical papers, theoretical studies, and literature reviews, see [65][66][67][68][69]. Within the field of RRI, key performance criteria are much less abundant in peer-reviewed, academic literature, but see [70].…”
Section: Rri Key Performance Indicators (Kpis)mentioning
confidence: 99%
“…Finally, an emphasis on the productive and transformative quality of socio-technical integration is the distinct focus of a coordinated series of studies supported by the National Science Foundation and managed by the Center for Nanotechnology in Society at Arizona State University (e.g., Conley, 2011;Ellwood and Pandza, forthcoming;Fisher, 2007;Flipse et al, 2012;Schuurbiers, 2011). Thus, while similar tensions between public-ethical and national-industrial values can be observed, they appear to play out differently in the US, where the mechanism of socio-technical integration is distinguished from other ethics modes and governance considerations, and in the EU, where the said tension can be more readily located within the mechanism of socio-technical integration itself-at least judging from European policy discourse and the solicitations in our sample.…”
Section: Integrated Research In the United Statesmentioning
confidence: 99%
“…For integration would appear to be unlikely insofar as it has the aspiration if not the potential to "open up" (Stirling, 2008) scientific practices to more diverse social perspectives and productively disrupt science and innovation practices (Wynne, 2011). Indeed, there is increasing evidence for the productive if not transformative capacity of embedded insights and critiques from social scientific and humanistic perspectives to modulate core R&D practices (e.g., Fisher, 2007;Flipse et al, 2012;Ribes and Bowker, 2009;Schuurbiers, 2011). 17 In this case, we cautiously suggest that substantive forms of socio-technical integration are able, or are at least perceived by scientists and policy makers to be able, to contribute to more "robust" (Nowotny et al, 2001) forms of knowledge and technological development, especially if they offer "dual value," meaning that critical reflection can also support learning that in turn promotes creativity and innovation (Fisher and Mahajan, 2006b, p. 6).…”
Section: Implications For Integrated European Researchmentioning
confidence: 99%